Constraint analysis and performance evaluation of participatory agri-aquaculture in watersheds - Mohanty, Rajeeb K; Mishra, A; Ghosh, S; Patil, D U (Indian Journal of Fisheries, 2012)
The present study was undertaken at the watershed level to identify the major constraints in adopting/developing participatoryagri-aquaculture and to make technological interventions with low input-based scientific aquaculture practices. The constraintanalysis through preferential ranking technique delineated as many as nine constraints with Rank Based Quotient valuesranging between 19.05 (priority to domestic use) to 100.0 (lack of awareness and technical knowledge) in all the three studylocations. After problem identification, an attempt was made to improve the existing agri-aquaculture practices with communityparticipation. Under the participatory intervention, fish yield was enhanced from 0.26-0.3 t ha-1 (before intervention) to0.94-1.72 t ha-1 (after intervention), while the net water productivity of water harvesting structures ranged betweenRs. 4.7-5.35 m-3. The return from rabi crop was highly encouraging and farmers had additional income. Economic analysisof the interventions clearly showed that the fish culture along with agriculture activity (post-intervention) enhanced theannual income of the farming community by Rs. 3561 - Rs. 12533 per hectare. Further, utilisation of water from the waterharvesting structures (WHSs) during rabi crop enhanced the cropping intensity from 100 to 137%. As in the present study,scientific approach with low input-based participatory aquaculture and multiple use of water would certainly enhance theoverall crop productivity, cropping intensity, water productivity and income.